Pusat Penelitian dan Pengembangan Sosial Ekonomi Pertanian, Bogor - WAHYUNI, SRI (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
This paper describes approaches in providing a chance to people to participate in the agricultural development. The paper consist of four steps namely:1) Introduction activities that should be carried out before implementing the PRA. such as recognizing each other between field staffs and farmers and socialization of the program. 2) Steps and the principles of PRA. 3) . Increasing the participation of people throught structural approaches and 4) Increasing the participation of people through structural approaches. It is concluded that to increase the agricultural development , the implementation of PRA is definitely needed. There are three steps and 20 principles of PRA method that should be followed in implementing PRA. Before implementing PRA, recognition and program socialization are needed. In order to get success program, a manual of the program should be prepared. The steps and principles of the PRA should be implemented based on the specific location. To increase the development of agriculture, field staffs should be understand well about the structure and culture of the target village.ngembangan Sosial Ekonomi Pertanian, Bogor
Keywords: Agricultural Development, Participation and Society